2019
DOI: 10.1016/j.clcc.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Scope of Photothermal Therapy–Based Nanomedicines in Preclinical Models of Colorectal Cancer

Abstract: Oncological thermal ablation involves the use of hyperthermic temperatures to damage and treat solid cancers. Thermal ablation is being investigated as a method of treatment in colorectal cancers and has the potential to complement conventional anti-cancer treatments in managing local recurrence and metastatic disease. Photothermal therapy utilises photosensitive agents to generate local heat and induce thermal ablation. There is growing interest in developing nanotechnology platforms to deliver such photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…The same phenomenon is reported for other metals, such as silver, platinum, copper, palladium [22,51,53], iron oxide, quantum dots and rare-earth ion-doped photoluminescent NPs [53,61,114].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The same phenomenon is reported for other metals, such as silver, platinum, copper, palladium [22,51,53], iron oxide, quantum dots and rare-earth ion-doped photoluminescent NPs [53,61,114].…”
supporting
confidence: 76%
“…These effects induce the cells to apoptosis. Instead, necrosis occurs when the temperature is over 50 °C [51,52]. Cancer cells are more susceptible to the temperature rise because of their impaired vasculature that reduces their ability to face a change in the homeostasis conditions.…”
Section: Radiofrequency Responding Npsmentioning
confidence: 99%
“…In healthy tissue at temperatures of up to 45 °C, vasculature readily increases the blood flow which dispels heat. [ 152 ] On the other hand, tumor vasculature is hyperpermeable, disorganized, and often have excess blind ends and abnormal bulges, making them greatly inefficient in heat dissipation. Thus, at the same thermal dose, the healthy tissue can remain at a lower temperature than the tumor.…”
Section: Summarizing Remarksmentioning
confidence: 99%
“…Although PTT is still in early stage of development, the application of light-induced heating nanoparticles is of great interest in the area of modern nanomaterials for cancer therapy. [19][20][21] What is more, it has been shown that combined chemo-and photothermal therapy leads to improved therapeutic effect and diminishes the probability of cancer regression. 22 It has been demonstrated that both bare magnetic nanoparticles and magnetic spheres show weak photothermal responses so their photothermal properties have to be enhanced in order to fully exploit the potential of these magnetic nanostructures in advanced cancer therapy.…”
Section: Introductionmentioning
confidence: 99%